2023
DOI: 10.14488/bjopm.1494.2023
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing SMEs Performance through Supply Chain Collaboration and moderation of Supply Chain Technology Implementation

Abstract: Goal: The minimal inter-firm resource sharing has raised problems for small and medium-sized enterprises (SMEs). There has been little focus on a thorough understanding of supply chain collaboration in the context of SMEs in Pakistan. This research looks into the antecedent impact of governance mechanisms and collaborative culture on supply chain collaboration (SCC), as well as the direct influence of supply chain collaboration on SMEs' performance in developing countries. Design/Methodology/Approach: The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…According to Imtiaz et al (2023), they showed significant and well-founded results, demonstrating that supply chain connectivity has a significant effect on performance. Supply chain connectivity allows companies to share the resources they own with other companies and in return use the remaining resources they have.…”
Section: Figure 1 Data On Natural and Synthetic Traditional Fashion P...mentioning
confidence: 99%
“…According to Imtiaz et al (2023), they showed significant and well-founded results, demonstrating that supply chain connectivity has a significant effect on performance. Supply chain connectivity allows companies to share the resources they own with other companies and in return use the remaining resources they have.…”
Section: Figure 1 Data On Natural and Synthetic Traditional Fashion P...mentioning
confidence: 99%